Influence of Student Behavior on Hepatitis A Incidence and Prevalence in Islamic Boarding School “Sidogiri” - Bhirawa Odie Prino Secaria; Lilis Sulistyorini; Soedjajadi Keman (Humanistic Network for Science and Technology (HNST), 2018)
Islamic boarding school Sidogiri is one of the school which has 8.400 male students. The sanitary conditions of Islamic boarding school are closely related to the contagion rate of contagious environment-based diseases, one of which is Hepatitis A. Islamic boarding school Sidogiri experiencing Hepatitis A outbreak in 2014, attacked as many as 111 students. This research was conducted to find out the correlation between students behavior (knowledge, attitude, and action) with incident and prevalence of Hepatitis A. The type of research was analytic observational research by analyzing behavior with the occurrence of Hepatitis A (IgG and IgM). The study was conducted in Islamic boarding school Sidogiri Kraton subdistrict in Pasuruan district from July 2017 until March 2018. The population in this study were all students in Islamic boarding school Sidogiri. Sample selection was done randomly so that got sample amount 38 people. The result of this research mentioned that attitude and action factor have significant influence to the occurrence of hepatitis A (IgG) with p-value equal to 0.017. The lower the attitudes and actions, the higher the prevalence of IgG. While the action factor has a significant effect on the incidence of Hepatitis A (IgM) with p value of 0.001. The lower the action, the higher the prevalence of IgM. Socialization, promotion and health education needs to be done to reduce the risk of contracting hepatitis A. Keywords: Islamic boarding school; students behaviour; hepatistis A; IgG; IgM